A tannic acid doped hydrogel with small extracellular vesicles derived from mesenchymal stem cells promotes spinal cord repair by regulating reactive oxygen species microenvironment. (December 2022) - Liu, Zhong; Guo, Song; Dong, Lanlan; Wu, Peipei; Li, Kewei; Li, Xinhua; Li, Xiang; Qian, Hui; Fu, Qiang
Abstract: Spinal cord injury (SCI) is a serious disease of the central nervous system that is associated with a poor prognosis; furthermore, existing clinical treatments cannot restore nerve function in an effective manner. Inflammatory responses and the increased production of reactive oxygen species (ROS) in the microenvironment of the lesion are major obstacles that inhibit the recovery of SCI. Small extracellular vesicles (sEVs), derived from mesenchymal stem cells, are suitable options for cell-free therapy and have been shown to exert therapeutic effects in SCI, thus providing a potential strategy for microenvironment regulation. However, the effective retention, controlled release, and integration of small extracellular vesicles into injured spinal cord tissue are still a major challenge. Herein, we fabricated an N-acryloyl glycinamide/gelatin methacrylate/Laponite/Tannic acid (NAGA/GelMA/LPN/TA, NGL/T) hydrogel with sustainable sEV release (sEVs-NGL/T) to promote the recovery of motor function after SCI. The newly developed functional sEVs-NGL/T hydrogel exhibited excellent antioxidant properties in an H2 O2 -simulated peroxidative microenvironment in vitro . Implantation of the functional sEVs-NGL/T hydrogel in vivo could encapsulate sEVs, exhibiting efficient retention and the sustained release of sEVs, thereby synergistically inducing significant restoration of motor function and urinary tissue preservation. These positive effects can be attributed to the effective mitigation of the inflammatory and ROS microenvironment. Therefore, sEVs-NGL/T therapy provides a promising strategy for the sEV-based therapy in the treatment of SCI by comprehensively regulating the pathological microenvironment. Graphical abstract: Image 1